Literacy Quality in Static Archive Services: A Study at the Yogyakarta Library and Archives Service - Ismaya; Galib, Andi Ahmad Chabir; Ridwan, Madinatul Munawwarah; Aminullah, Andi Muhammad; Nuryani, Siti; Masnur, Masnur; Sitonda, Syawal (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study evaluated the quality of static archive services at the Yogyakarta Library and Archives Service, Indonesia. The research adopted a mixed-methods approach, combining quantitative and qualitative methodologies. The population comprised employees managing static archives within the institution, with a sample of 13 respondents selected through a saturated sampling technique. Data were collected using questionnaires and interviews and analyzed through descriptive and inferential statistical methods, including a one-sample t-test and correlational analysis. The findings revealed that the quality of archival facilities, employee competence, and performance effectiveness significantly influence the overall quality of archival services, with each variable hypothesized to meet at least 70% of the standard benchmarks. These insights underscore the critical areas for service improvement and highlight the need for targeted strategies to enhance institutional outreach and engagement. The study may contribute to the academic discourse on archival services by providing empirical evidence on the factors affecting service quality. Furthermore, it offers actionable recommendations for archival institutions to enhance service delivery and fulfill their mission of preserving and disseminating archival knowledge.